Twin deficits revisited: A role for fiscal institutions? - Afonso, António (2022)
We revisit the twin-deficits relationship for a sample of 65 countries with fiscal rules over the period 1985–2015, using a panel data estimation methods. Our analysis accounts for the role of various types of fiscal rules and institutions: expenditure rules, revenue rules, budget balance rules, debt rules, fiscal councils, and supporting procedures. We find that the twin-deficits hypothesis is confirmed. The impact of the budget balance on the current account balance is increased when fiscal rules are considered, except with revenue rules and debt rules. Well-designed fiscal rules, fiscal councils and features that reinforce compliance with rules improve the current account balance. Our findings highlight the role of fiscal factors in explaining sustained global current account imbalances. They also contribute to the ongoing discussion about the improvement of macroeconomic and budgetary surveillance in the European context.